Derivation of tidal constituents from satellite altimetry data for coastal vulnerability assessment in Malaysia [electronic resource] - Adzlan Ainee, 1989-, author 602629 (Skudai : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2016